حكم دفع القيمة في الزكاة آثاره الاقتصادية وقواعده الفقهية (Damascus University Journal for legal sciences, 2022)
This research aims to explain the rule of paying the value instead of the same due in zakat, it studies the economic effects resulting from saying that it is permissible to pay the value in zakat, and explains the jurisprudential rules that regulate paying the value in zakat, as well as linking the jurisprudence rules to the Economics, because this is very important to know the Islamic ruling about contemporary financial transactions, and there is a great benefit to link the economy to Islamic jurisprudence, so that financial transactions are governed by the rules of Sharia.This research has found multiple results, including that: there is no disagreement among the jurists about the permissibility of paying the value in trade goods, but they have differed in non-commercial goods, and the reason for this difference is that they differ in the predominant meaning of Zakat: pure obedience or financial worship.Consequently an important issue appeared, that is clearing the obligation before Allah from the payment of Zakat.  The researcher also concluded that paying the value in zakat has many economic implications, including reducing government expenditures, decrease consumption, and investment promotion. There are juristic rules that govern the issue of paying value in zakat, such as the rule: “hardship brings convenience”, the rule: “The need is like the necessity, whether it is a public or a private”, the rule: “The value of zakat is only taken in particular cases”, and the rule: “The basic principle is that zakat is regarded as What is in the texts of Sharia in particular”.